(3GdeQcR GdbGfhfj dQFjS GdOhdI OHdheGSjG (B:s (3OQGSI ebGQfI Hjf GdbGfhf GdOHdheGSj hGdOHdheGSjI GdESdGejI (B/s - (3GdMOjKj, eMeO MSf MejOs ((3GdEScfOQjI, eUQ (B:s (3GdecJH GdLGeYj GdMOjK,s, 2014)
(3jJfGhd cJGH (B((3GdeQcR GdbGfhfj dQFjS GdOhdI OHdheGSjG (B: (3OQGSI ebGQfI Hjf GdbGfhf GdOHdheGSj hGdOHdheGSjI GdESdGejI(B) (3hGdPj bGe HJCdjag (B"(3eMeO MSf MejO GdYdj GdMOjKj(B" (3aj MhGdj (B(216) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdfXGe GdSjGSj aj GdESdGe(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3GdUaI GdJeKjdjI dQFjS GdOhdI, GdGYJQGa HQFjS GdOhdI MSH WHjYI GdfXe GdSjGSjI, GdaUd GdKGfj (B: (3MUGfGJ QFjS GdOhdI, GdMUGfI GdTNUjI, GdeGdjI, GdbVGFjI, GdSjGSjI, GdMUGfGJ aj GdfXGe GdESdGej, GdaUd GdKGdK (B: (3GeJjGRGJ QFjS GdOhdI, GdGeJjGRGJ GdeGdjI, GdeUGOQ hGdCSS GdbGfhfjI ddMUGfGJ hGdGeJjGRGJ GdOHdheGSjI, GdeQGSe hGdeLGedGJ GdOHdheGSjI, GdOHdheGSjI aj YgO GdfHj eMeO Udi Gddg Ydjg hSde(B.s
(3JUeje GdZdGa (B: (3QMGH(B.s
(3eUWdMGJ (B: (3UaMI (B187-204.s
(3HHdjhLQGajI (B: (3UaMI (B205-212.s
Keywords: (3GdfXGe GdSjGSj aj GdESdGes; (3QDSGA GdLeghQjIs -- (3hVY bGfhfj, bhGfjf, EdN(B.s; (3fXe GdMce aj GdESdGes